Analysis of clinical pharmacist interventions in the COVID-19 units of a French university hospital. (11th March 2021) - Perez, Maxime; Masse, Morgane; Deldicque, Anne; Beuscart, Jean Baptiste; De Groote, Pascal; Desbordes, Jacques; Fry, Stéphanie; Musy, Elodie; Odou, Pascal; Puisieux, Francois; Lambert, Marc; Scherpereel, Arnaud; et al.
Abstract : Objectives: The objectives were to compare clinical pharmacist interventions between two care groups: COVID-19-positive and COVID-19-negative patients, and to identify drugs that require particular attention, especially those involved in COVID-19 management. Methods: A prospective cohort study was conducted on patients with positive and negative COVID-19 statuses admitted to Lille University Hospital over 1 month. Pharmaceutical analysis instigated interventions to rectify drug-related errors. For each pharmaceutical intervention (PI), the anatomical therapeutic chemical classification of the drug and the outcome of such an intervention were specified. Results: The study included 438 patients. Prescription analysis led to 188 PIs performed on 118 patients (64 COVID-19-positive patients and 54 COVID-19-negative patients). Most drug-related problems were incorrect dosage representing 36.7% (69/188) of all interventions: 27.9% (29/104) for the COVID-19-positive group and 47.6% (40/84) for the COVID-19-negative group. The most frequent PI in 34% (64/188) of cases was terminating a drug: 27.9% (29/104) for the COVID-19-positive group and 47.6% (40/84) for the COVID-19-negative group. The main drug classes involved were antithrombotic agents (20.7%, 39/188), antibacterials for systemic use (13.8%, 26/188) and drugs for gastric acid-related disorders (6.4%, 12/188). Study population was limited to a single centre over 1 month. Conclusion: No difference in PI was noted between the two groups. The presence of pharmacists led to a reduction in drug-related prescription problems, especially for antithrombotic and antibacterial drugs for both groups. Clinical pharmacy commitment in such a pandemic is therefore important.